Is the fixation of single incision TVT-S tape as good as that of transobturator tape? An ultrasound study of randomized trial results - Serdinsek, Tamara; Martan, Alois; Svabik, Kamil; But, Igor; Kolek, Petr; Masata, Jaromir (International urogynecology journal, 2021)
INTRODUCTION: TVT-Secur (TVT-S) was the first single-incision sling available on the market and was soon found to have less efficacy than mid-urethral slings. Our aim was to assess the position and tape descent following TVT-O and TVT-S H in a U procedure and, based on this evaluation, to find the possible reason for lower TVT-S surgery efficacy. METHODS: We conducted an ultrasound study of a randomised trial with a 3-year follow-up that took place between 2007 and 2009 and included 197 women with urodynamic stress urinary incontinence. Of these, 67 were allocated to receive the TVT-O procedure, 64 to TVT-S in the H position, and 65 in the U position. Patients underwent a complete urogynaecological and ultrasound examination. The positions of the bladder neck and the tape after surgery were assessed and the data obtained compared between groups. RESULTS: Our primary study showed a significantly higher rate of positive stress tests in the TVT-S groups compared to the TVT-O group. After surgery, there was no difference between the position of the tape at rest and at maximal Valsalva between the groups. In TVT-O patients, the mean length of the upper tape margin descent increased from 6 mm on the 1st day after surgery to 9 mm 3 months after surgery and remained stable afterwards. For TVT-S patients, there was a further increase of up to 15 mm in tape descent after 3 months. CONCLUSIONS: Our results show that the lower efficacy of TVT-S might be due to inadequate fixation and increasing tape descent.
Keywords: Ultrasound study; Treatment failure; Humans; suburetrální pásky; Trans-obturator tape; Urodynamics; urodynamika; Female; močový měchýř; Ultrasonography; výsledek terapie; lidé; Suburethral Slings; Urinary Incontinence, Stress; stresová inkontinence moči; ultrasonografie; ženské pohlaví; Single-incision slings; Urinary Bladder; Treatment Outcome; Stress urinary incontinence; TVT-S